Pendampingan Digitalisasi Usaha dan Penguatan Kelembagaan Kelompok Usaha Bersama (KUB) Pengrajin Pandai Besi dalam Menghadapi Persaingan ‎Industri Modern - Angga Adigara; Zainal Hakim; Muhammad Imamul Muttaqin Arisandhi; Khodimul Wahib; Muhammad Zaini; Abdul Wahid (LPPPM STAI Darul Hikmah Bangkalan, 2026)
The blacksmithing industry is a hereditary microenterprise sector that supports ‎household livelihoods in Dupok Village, but it continues to face low digital literacy and ‎conventional marketing practices. This community service program aimed to strengthen ‎business digitalization capacity and the institutional capacity of a Joint Business Group ‎‎(Kelompok Usaha Bersama/KUB) involving 25 blacksmith partners. A Participatory ‎Action Research (PAR) approach was implemented through five cycles: problem ‎identification, action planning, action implementation, monitoring, and reflection. ‎Evaluation used pre- and post-program questionnaires, monitoring observation sheets, ‎and focus group discussions. Results indicate increases in social media use (32% to ‎‎76%), active marketplace accounts (16% to 64%), financial record-keeping (24% to ‎‎72%), digital catalog ownership (8% to 68%), and out-of-region sales (20% to 48%). ‎Average monthly orders rose from 12 to 18, and average monthly revenue increased ‎from IDR 2,500,000 to IDR 3,100,000. Partner satisfaction ranged between 76% and ‎‎88%. These findings indicate a positive trend in digital capacity and business ‎performance, although institutional strengthening of the KUB remains at an early stage ‎and requires continued mentoring.